2020
DOI: 10.1002/ece3.6257
|View full text |Cite
|
Sign up to set email alerts
|

The limit of resistance to salinity in the freshwater cyanobacterium Microcystis aeruginosa is modulated by the rate of salinity increase

Abstract: The overall mean levels of different environmental variables are changing rapidly in the present Anthropocene, in some cases creating lethal conditions for organisms. Under this new scenario, it is crucial to know whether the adaptive potential of organisms allows their survival under different rates of environmental change. Here, we used an eco‐evolutionary approach, based on a ratchet protocol, to investigate the effect of environmental change rate on the limit of resistance to salinity of three strains of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Under culture conditions, Microcystis growth is largely affected by conditions such as salinity and nutrients (Martinez et al 2017;Georges et al 2019). Melero-Jiménez et al (2020) demonstrated that M. aeruginosa had a limit of resistance to salinity increases. High salinity can result in the release of high levels of inorganic phosphorus from sediments and change nitrogen retention and cycling in coastal freshwater (Ardón et al 2013;Williams et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Under culture conditions, Microcystis growth is largely affected by conditions such as salinity and nutrients (Martinez et al 2017;Georges et al 2019). Melero-Jiménez et al (2020) demonstrated that M. aeruginosa had a limit of resistance to salinity increases. High salinity can result in the release of high levels of inorganic phosphorus from sediments and change nitrogen retention and cycling in coastal freshwater (Ardón et al 2013;Williams et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The isolated strains have not been tested for presence of genes against salt stress, but they evidently were capable of coping with higher salinity as both strains were maintained in normal WC medium for months before the experiment was conducted. The gradual increase in salinity (4‰ per 7 days) may have favoured adaptation to higher salinities [ 44 ], which seems a more likely scenario in natural environments than a shockapproach of immediately transferring cells from the WC medium (0.5‰) to high salinities of 12‰ and 16‰. A replacement of salinity-sensitive cells by salinity-resistant mutants in M. aeruginosa was less likely, because with 10 −7 –10 −6 mutants per generation [ 45 ], a sharp decline in biomass would have occurred when salinity was increased.…”
Section: Discussionmentioning
confidence: 99%
“…The ratchet protocol through which the resistant strains were isolated (Martín-Clemente et al 2019 ) is not designed to elucidate the mechanism (acclimation vs. adaptation) allowing the increase in tolerance. Therefore, a complementary experiment (Rouco et al 2014 ; Melero-Jiménez et al 2019 , 2020 ) was carried out with the derived strains. This protocol relies on the assumption that, at least in bacteria, the acclimation process could last as much as 2–3 generations (Bennett and Lenski 1997 ).…”
Section: Methodsmentioning
confidence: 99%
“…caused by acclimation). Nevertheless, this question can be analysed using a complementary experimental evolutionary design (Rouco et al 2014 ; Melero-Jiménez et al 2019 , 2020 ). On the other hand, if the resistance is due to an adaptation process a physiological cost of the mutation conferring tolerance in terms of lower growth rates in the absence of the selective agent is expected (Lenski 1998 ).…”
Section: Introductionmentioning
confidence: 99%